Respuesta :

By the ratio test, the first series converges if

[tex]\displaystyle \lim_{k\to\infty} \left|\frac{\frac{x^{k+1}}{k+10}}{\frac{x^k}{k+9}}\right| = |x| \lim_{k\to\infty} \frac{k+9}{k+10} = |x| < 1[/tex]

while the second series converges if

[tex]\displaystyle \lim_{k\to\infty} \left|\frac{(k+1)(k+5)x^{k+1}}{k(k+4)x^k}\right| = |x| \lim_{k\to\infty} \frac{k^2+6k+5}{k^2+4k} = |x| < 1[/tex]

So as long as |x| < 1, we have

[tex]\displaystyle h(x) = -(x+4) f(x) + 7x^2 g(x)[/tex]

Distribute f(x) :

[tex]\displaystyle h(x) = -x f(x) - 4 f(x) + 7x^2 g(x)[/tex]

Substitute f and g with their series representations:

[tex]\displaystyle h(x) = -x \sum_{k=0}^\infty \frac{x^k}{k+9} - 4 \sum_{k=0}^\infty \frac{x^k}{k+9} + 7x^2 \sum_{k=0}^\infty k(k+4)x^k[/tex]

Simplify the powers of x :

[tex]\displaystyle h(x) = -\sum_{k=0}^\infty \frac{x^{k+1}}{k+9} - 4 \sum_{k=0}^\infty \frac{x^k}{k+9} + 7 \sum_{k=0}^\infty k(k+4)x^{k+2}[/tex]

Shift the index in each sum as needed so that each one is written in terms of [tex]x^k[/tex] :

[tex]\displaystyle h(x) = -\sum_{k=1}^\infty \frac{x^k}{k+8} - 4 \sum_{k=0}^\infty \frac{x^k}{k+9} + 7 \sum_{k=2}^\infty (k-2)(k+2)x^k[/tex]

Pull out as many terms as needed from each sum so that they each start with the same index:

[tex]\displaystyle h(x) = -\left(\frac x9 + \sum_{k=2}^\infty \frac{x^k}{k+8}\right) - 4 \left(\frac19 + \frac x{10} + \sum_{k=2}^\infty \frac{x^k}{k+9}\right) + 7 \sum_{k=2}^\infty (k-2)(k+2)x^k[/tex]

Condensing the series gives

[tex]\displaystyle h(x) = -\frac49 - \frac{23}{45}x + \sum_{k=2}^\infty \left(7(k-2)(k+2)-\frac1{k+8} - \frac4{k+9}\right)x^k[/tex]

So, if

[tex]\displaystyle h(x) = \sum_{k=0}^\infty c_kx^k = c_0 + c_1x + c_2x^2 + \cdots[/tex]

then it follows that

[tex]c_0 = -\dfrac49[/tex]

[tex]c_1 = -\dfrac{23}{45}[/tex]

and for k ≥ 2,

[tex]c_k = \displaystyle 7(k-2)(k+2)-\frac1{k+8} - \frac4{k+9}[/tex]

ACCESS MORE